The impacts of long‐lived jet contrail 'outbreaks' on surface station diurnal temperature range. (14th March 2015) - Bernhardt, Jase; Carleton, Andrew M.
ABSTRACT: Multiple persistent jet aviation contrails – contrail 'outbreaks' – occur frequently over certain portions of the Continental United States (CONUS). The artificial cloudiness generated by contrail outbreaks alters the atmospheric radiation budget, potentially impacting the surface air temperature, particularly the diurnal temperature range (DTR), or difference between daytime maximum and nighttime minimum temperatures. This study evaluates the hypothesis that contrail outbreaks reduce the DTR relative to clear‐sky conditions. We utilize a database of longer‐lived (>4 h duration) jet contrail outbreaks for the CONUS previously determined from interpretation of high‐resolution satellite imagery, for the January and April months of 2008 and 2009. The outbreak impact on DTR was determined by comparing maximum and minimum temperatures at pairs of surface weather stations (one outbreak and one non‐outbreak) across two regions of climatologically high outbreak frequency; the South in January, and Midwest in April. We ensured that each station pair selected had broadly similar land use‐land cover, soil moisture, and synoptic air mass conditions. For outbreaks in the South (January), there was a statistically significant reduction of DTR at the outbreak versus non‐outbreak stations. This result was similar to that obtained for a smaller subset of outbreaks for which lower‐level clouds could be confirmed as being absent (from North American Regional Reanalysis (NARR) output). For the Midwest (April), the results are mixed; statistically different for satellite‐retrieved outbreaks, but not significantly different for the NARR‐validated dataset. These results suggest that persistent jet contrails should be considered in short‐term weather forecasting, and for their potential influence on the climatology of more frequently impacted areas.